Strategi Penjualan untuk Meningkatkan Daya Jual Pabrik Tahu Sumedang dengan Pemasaran Islam - Permana, Muhamad Bintang; Koni, Agus; Kurniawan, Wawan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The problems in this study are (1) How is the implementation of sales strategies to increase selling power at the Sumedang tofu factory in Malandang block, Subang Subdistrict with Islamic marketing? The method used is qualitative research. Data collection techniques that will be used are observation, interview, and documentation. From the results of the study, the authors observed the sales strategy with a review of Islamic marketing at the Sumedang tofu factory. The result is that the marketing strategy needs to improve in terms of promotion because it is still traditional, and the review of Islamic business ethics is appropriate. The results of this research are sourced from a literature review with data collection through books, journals, and articles. The data collected is analyzed qualitatively. In the economic system, marketing is an important thing to do to achieve product sales targets so that businesses can succeed. To achieve business targets, there are some market players who do not pay attention to marketing ethics. In Islam, Rasulullah has taught business ethics, among others, about marketing through the nature of Rasulullah which is abbreviated as SAFT (shiddiq, amanah, fathanah and tabligh). In addition, marketers must pay attention to theistic ethics (rabbaniyyah), Ethical (akhlaqiyyah), Realistic (al-waqiyyah), and humanistic (insaniyyah). By paying attention to the concept of marketing in Islam, it is hoped that there will be no market.